(untitled) (Journal of Health, Population and Nutrition, 2010)
The study aimed at verifying the associated factors of self-perceived body changes in adults living with HIV in highly-active antiretroviral therapy (HAART) in the city of São Paulo, Brazil. This cross-sectional study was conducted among people living with HIV on HAART for at least three months. A standardized questionnaire was used for assessing self-perceived body changes. Associated factors relating to self-reported body changes in people living with HIV (PLHIV) were assessed with Student’s t-test and chi-square test. In total, 507 patients were evaluated. The mean time since diagnosis was 6.6 years [standard deviation (SD)±4.1], and the mean duration of HAART was 5.1 years (SD±3.3). Self-perceived body changes were reported by 79.5% of the participants and were associated with viral load and duration of HAART. Fibre intake was lower among males who gained in abdominal fat (p=0.035). HAART-related body changes were reported by the large majority of the population and were associated with demographic and clinical variables. Key words: Body-weight; Cross-sectional studies; Diet; HAART; HIV; Perceptions; Brazil DOI: 10.3329/jhpn.v28i6.6604 J HEALTH POPUL NUTR 2010 Dec;28(6):560-566